Visualisasi Gedung Sekolah 3D dengan Konsep Virtual Reality Berbasis Android - Dewantoro, Danang; Andryana, Septi; Gunaryati, Aris (STMIK Budi Darma, 2020)
Promotion and introduction of school buildings still uses media such as brochures or pamphlets, because it requires software that can introduce and provide information about specific school buildings in SMK 25 Jakarta. This study aims to provide an introduction to the Virtual Reality 25 Jakarta Vocational High School building using the VR Box as a medium of information about the rooms to prospective new students. This application utilizes the method of research and development (R&D) with the ADDIE model, this model serves to carry out periodic assessments in each phase so that the resulting product becomes valid. The validation test results concluded that the system is valid. Testing the level of user satisfaction after using the Virtual Reality application SMKN 25 Jakarta can be concluded that the average user gives a value of 3.4 or enough on the satisfaction of the application menu display, and gives a value of 3.05 on the satisfaction of virtual mode.